Will Vinton's Claymation Christmas [videorecording (DVD)] : plus Halloween & Easter celebrations - Diener, Paul; Vinton, Will; Altschul, David; Bruce, Barry; Gustafson, Mark; Holznagel, Ryan; Liddle, Ralph; Conner, Tim; Cummings, Brian; Fairchild, Krisha; Tolces, Todd; Counterfit, John (Hen's Tooth Video, 2003)
[Claymation comedy of horrors] Wilshire Pig and Sheldon Snail a map to Doctor Frankenswine's monster [Claymation Christmas celebration] Two prehistoric dinosaurs guide you through a small town Christmas celebration [Claymation Easter] The villainous Wilshire Pig has kidnapped the Easter Buny and will stop at nothing to become his replacement.